Optimization of Audience-Based Digital Da’wah and Counseling - Kinanti Sonyaning Ratri; Sabina Amroh Diyanati (Proceedings Of International Conference On Islamic Counseling Studies (ICONICS), 2025)
The development of digital technology has changed the way preaching and counseling are carried out, from conventional methods to a more flexible, interactive, and wide-reaching digital approach. This study aims to analyze strategies for optimizing audience-based digital preaching and counseling by emphasizing the importance of segmentation, communication strategies, and the use of media that is appropriate to the characteristics of the target audience. The research method uses a qualitative approach through a literature study with secondary data analysis sourced from journals, books, and related documents. The results of the study show that the effectiveness of digital da’wah and counseling is greatly influenced by the ability to recognize audience needs, the use of clear language, persuasive narratives, attractive visuals, and varied content formats such as short videos, podcasts, Instagram carousels, and digital posters. In addition, the application of empathy, a participatory approach, and a non-judgmental attitude are key to success in building emotional connections with audiences and counselees. Evaluation of digital strategies based on indicators of behavioral change, audience engagement, and counselee satisfaction is also necessary for continuous development. Thus, audience-based digital da’wah and counseling can be an effective, relevant, and adaptive strategy in facing communication challenges in the modern era.